Teknik Pengolahan, Pengemasan Produk dan Strategi Pemasaran Abon Telur di Kelompok Wanita Kelurahan Pager, Kecamatan Rakumpit, Kota Palangka Raya: The Processing and Packaging of Egg’s Abon Product in the Women's Group of Pager Village, Rakumpit District, Palangka Raya City - Yuanita, Iis; Silitonga, Lisnawaty; Nopembereni, Eti Dewi; Nainggolan, Depris; Ginting, Evi Tiodora; Saragih, Risky Junidman; Simbolon, Yoges (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The objectives to be achieved are the diversification of animal products originating from ducks into egg Abon products and the development of small industries in women's groups to produce processed egg Abon products that can meet local and regional demand to increase family or group income. Processing food products can increase sales value and profit by up to one hundred percent. The problem with the partner group is that they still need to learn how to process egg floss products and the touch of food product packaging technology and marketing strategies in partner areas. Several methods for solving problems include counseling and training regarding diversification of food products in the form of egg floss, packaging techniques using good packaging tools, marketing strategies for the products produced, as well as approaches through monitoring and evaluating activities with partner groups. The results that have been achieved are the implementation of counseling and training on making egg floss, good packaging techniques and marketing strategies have been implemented and the partners are very enthusiastic and intend to make egg floss one of their small businesses. Partner continues to strive and innovate in marketing, adding to the taste of the egg floss it produces.